2022
DOI: 10.3390/ijms23116177
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Crosslinked Hyaluronic Acid/Carboxymethyl Cellulose Composite Hydrogel as a Dural Substitute to Prevent Post-Surgical Adhesion

Abstract: A dural substitute is frequently used to repair dura mater during neurosurgical procedures. Although autologous or commercially available dural substitutes matched most of the requirements; difficulties during dural repair, including insufficient space for suturing, insufficient mechanical strength, easy tear and cerebrospinal fluid leakage, represent major challenges. To meet this need, a photo-crosslinked hydrogel was developed as a dural substitute/anti-adhesion barrier in this study, which can show sol-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…The HA/CMC hydrogel had good biodegradability, biocompatibility (>80% cell viability for 3T3 fibroblasts in vitro cultured for 24 h) and mechanical properties. In vivo experiments demonstrated that these hydrogels can act properly as dural substitutes to repair dural defects in rabbits [ 126 ].…”
Section: Methodsmentioning
confidence: 99%
“…The HA/CMC hydrogel had good biodegradability, biocompatibility (>80% cell viability for 3T3 fibroblasts in vitro cultured for 24 h) and mechanical properties. In vivo experiments demonstrated that these hydrogels can act properly as dural substitutes to repair dural defects in rabbits [ 126 ].…”
Section: Methodsmentioning
confidence: 99%
“…From the thermogravimetric analysis (TGA), it was observed that HD and HD-based cross-linked hydrogels generally exhibited two stages of weight loss (Figure S2). The initial weight loss occurred at approximately 100 °C, which was attributed to the evaporation of water molecules that were initially bound to the HD polysaccharide. , The weight loss between 200 and 350 °C reflected the thermal stability at high temperatures. Similarly, the maximum thermal degradation temperatures of HD-L and HD-H hydrogels changed compared with those of the native polysaccharide.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The isotropic surface properties of these substitutes are not well suited for cell attachment and proliferation, which results in poor performance of the material [ 74 ]. Among them, various tough hydrogels have been prepared, which possess a good load-bearing capacity to fit the desired mechanical properties for dural implants [ 53 , 82 , 83 , 84 , 85 , 86 , 87 ]. However, the poor biocompatibility and degradability of these synthetic polymers limit their application as a dural substitute.…”
Section: Biomedical Applications Of Electrospun Nanofibersmentioning
confidence: 99%